THE EFFECT OF USING LISTENING-READING-DISCUSSION (LRD) STRATEGY ON STUDENTS UNDERSTANDING OF READING NARRATIVE TEXT AT MTS PALASA - Cindy; Andi Muhammad Dakhalan; Dzakiah, Dzakiah (Datokarama English Education Journal, 2022)
The reading comprehension of grade IX students of MTs Palasa is still low, especially in reading narrative texts. so that the researcher was motivated to discuss the thesis entitled "The Effect of Using Listening-Reading-Discussion (LRD) Strategy on Students' Understanding of Reading Narrative Text at Mts Palasa". This research aims to obtain empirical evidence about the effect of using listening-read-discussion strategies on students' understanding of reading narrative texts. This research method is quantitative. The research design used is quasi-experimental. In the experimental class, the researcher used the listening-read-discuss method and in the control class, the researcher methods that are often used by teachers at the school, in 8 meetings with a time of 80 minutes for each class. The researcher used an instrument in the form of multiple choice. The instrument is given in pre-test and post-test. Before giving the treatment, the researcher gave a pre-test for the second class. Then after the treatment, the instrument was given in the form of a posttest. After giving the pre-test and post-test, the researcher analyzed the data using SPSS 25 to calculate the independent sample t-test. From the analysis of the data calculated using SPSS 25, this research shows differences in the value of the final significant mean between the classes, from the experimental class, was 70.00, while the final mean of the control class is 58.50. The hypothesis test shows that sig. 2 tailed (p) is 0.001 with alpha (α) is 0.05, so 0.002 < 0.05. It can be stated that Ho (Null Hypothesis) has been rejected and Ha (Alternative Hypothesis) was accepted. Therefore, it can be concluded that the use of listening-reading-discussion strategi affects the reading comprehension of ninth-grade students of MTs Palasa on narrative texts in the 2021/2022 academic year.